A novel approach for portal system reconstruction in liver transplant patients with grade IV portal vein thrombosis: Case study and literature review - Qu, Wei; Zhu, Zhi-Jun; Wei, Lin (Frontiers in Transplantation, 2022)
Background: Portal vein thrombosis is a common problem of end-stage liver disease in patients with portal hypertension and Yerdel grade Ⅳ thrombosis may be a contraindication for liver transplantation. Advances in surgical technique have indicated the feasibility of liver transplantation with PVT such as Reno-portal anastomosis, cavo-portal hemitransposition, but low graft portal blood perfusion and regional portal hypertension were the limitations. Methods: We introduce a new approach for portal system reconstruction in a patient underwent liver transplantation: A 28-year-old male was diagnosed with Budd-Chari syndrome and portal hypertension with grade Ⅳ portal vein thrombosis. Results: The “Pull-out” technique was applicated for thrombectomy, which can aid in exposing the superior mesenteric vein and portal vein branches and reducing technical difficulties associated with the identification and dissociation of surrounding anatomical structures. To collect sufficient portal vein blood perfusion and avoid regional portal hypertension, the portal vein system was reconstructed through double-approach procedure: Reno-portal anastomosis combined with portal-portal anastomosis. Conclusion: Based on a precision preoperative evaluation, application of the Pull-out technique and double-approach procedure may be an effective method of thrombectomy especially in cases of grade Ⅳ portal vein thrombosis.